PENGEMBANGAN AGROWISATA BALAI BENIH INDUK HORTIKULTURA KECAMATAN PEKALONGAN KABUPATEN LAMPUNG TIMUR - Dedeh Ismayanti; Nani Suwarni; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2014)
This study is conducted to determine the development strategy of attractions that exist in the Balai Benih Induk Hortikultura Agro tourism Pekalongan Subdistrict, East Lampung. It used survey method. The object of research was the development of Balai Benih Induk Hortikultura Agro tourism Pekalongan Subdistrict, East Lampung and the subject of research was Balai Benih Induk Hortikultura Agro tourism Pekalongan Subdistrict, East Lampung. Techniques of data analysis were done by using qualitative description, the data obtained would be analyzed using SWOT analysis. The results of this study are: (1) There are four types of alternative agro-tourism development strategy BBIH Pekalongan that needs to be done, namely, strategy SO (Strengths and Opportunities), Strategy WO (Weakness and oppotunities), Strategy ST (Strength and Threats), and Strategy WT (Weakness and Threaths). (2) The success of tourism development is determined by three factors, namely, the availability of objects and tourist attraction, their accessibility facilities are facilities and infrastructure, and the suit is the target of tourism facilities.Penelitian ini dilakukan untuk mengetahui strategi pengembangan objek wisata pada kawasan agrowisata Balai Benih Induk Hortikultura Kecamatan Pekalongan, Kabupaten Lampung Timur. Penelitian menggunakan metode survei. Objek penelitian adalah pengembangan objek wisata kawasan agrowisata BBIH Pekalongan dan subjek penelitian yaitu agrowisata BBIH Pekalongan. Teknik analisis data dengan cara deskriptif kualitatif, data akan dianalisis dengan analisis SWOT. Dari hasil penelitian diketahui yaitu: (1) Terdapat empat jenis alternatif strategi pengembangan agrowisata BBIH Pekalongan yang perlu dilakukan yaitu, strategi SO (Strength and Opportunities), strategi WO (Weakness and Oppotunities), strategi ST (Strength and Threats), dan strategi WT (Weakness and Threaths). (2) Keberhasilan pengembangan pariwisata ditentukan oleh 3 faktor yaitu, tersedianya objek dan daya tarik wisata, adanya fasilitas accessibility, dan terjadinya fasilitas amenities. Kata kunci: agrowisata, BBIH, pengembangan, strategi.